Characterization and Outcome of Two Pediatric Intensive Care Units with Different Resources - Rania G. Abdelatif; Montaser M. Mohammed; Ramadan A. Mahmoud; Mohamed A. M. Bakheet; Masafumi Gima; Satoshi Nakagawa (Critical Care Research and Practice)
Background. The pediatric intensive care units (PICUs) in developing countries have a higher mortality outcome due to a wide variety of causes. Identifying differences in the structure, patient characteristics, and outcome between PICUs with different resources may add evidence to the need for incorporating more PICUs with limited resources in the contemporary critical care research to improve the care provided for severely ill children. Methods. A retrospective study was conducted at Egyptian and Japanese PICUs as examples of resource-limited and resource-rich units, respectively. We collected and compared data of nonsurgical patients admitted between March 2018 and February 2019, including the patients’ demographics, diagnosis, PICU length of stay, outcome, predicted risk of mortality using pediatric index of mortality-2 (PIM-2), and functional neurological status using the Pediatric Cerebral Performance Category (PCPC) scale. Results. The Egyptian unit had a lower number of beds with a higher number of annual admission/bed than the Japanese unit. There was a shortage in the number of the skilled staff at the Egyptian unit. Nurse : patient ratios in both units were only similar at the nighttime (1 : 2). Most of the basic equipment and supplies were available at the Egyptian unit. Both actual and PIM-2 predicted mortalities were markedly higher for patients admitted to the Egyptian unit, and the mortality was significantly associated with age, severe sepsis, and PIM-2. The length of stay was shorter at the Egyptian unit. Conclusion. The inadequate structure and the burden of more severely ill children at the Egyptian unit appear to be the most important causes behind the higher mortality at this unit. Increasing the number of qualified staff and providing cost-effective equipment may help in improving the mortality outcome and the quality of care.